The effects of financial literacy, financial management and saving motives on financial well-being among working women - Sabri, Mohamad Fazli; Teo, Tze Juen (Malaysian Financial Planning Council, 2014)
The increased cost of living for Malaysians has made individuals and households more aware of the importance of managing their finances. The purpose of this study is (1) to identify the levels of financial literacy, financial management, saving motives and financial well-being of working women; (2) to explore the differences in financial well-being based on demographic characteristics of working women; (3) to identify the determinants of financial well-being among working women. The sample consisted of 447 women working in public agencies located in four states in Peninsular Malaysia, selected through the multi stage sampling technique. Data was collected through self-administered questionnaires. The results of this study show that respondents with moderate levels of financial literacy and financial well-being score a high level of financial management. There are statistically significant differences in financial well-being between married and single respondents (marital status), and between those with different educational levels (total years of education). There are significant relationships between financial literacy, financial management and saving motives with financial well-being. Demographic characteristics (age, educational level and marital status), financial literacy, financial management, and saving motives have significant influence on financial well-being as saving motives are a major contributing factor to financial well-being in terms of independent variables. Overall, age is the greatest predictor of financial well-being among working women.